Transition 2.0 Re-establishing Constitutional Democracy in EU Member States - Bobek, Michael; Bodnar, Adam; Bogdandy, Armin von (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, 2023)
The central question of Transition 2.0 is this: what (and how) may a new government do to re-establish constitutional democracy, as well as repair membership within the European Union, without breaching the European rule of law? This volume demonstrates that EU law and international commitments impose constraints but also offer tools and assistance for facilitating the way back after rule of law and democratic backsliding. The various contributions explore the constitutional, legal, and social framework of 'Transition 2.0'.